Sunburn incidence of apples is affected by rootstocks and fruit position within the canopy but not by fruit position on the cluster - Racskó, J.; Szabó, Z.; Miller, D. D.; Soltész, M.; Nyéki, J. (International Journal of Horticultural Science, 2009)
Authors investigated sunburn incidence of apples on the combinations of three different growth inducing rootstocks (M.9,MM.106 and seedling) and five varieties (‘Smoothee’, ‘Golden Reinders’, ‘Granny Smith’, ‘Gloster’ and ‘Jonagold Jonica’). Symptoms were classified as sunburn browning, sunburn necrosis and photooxidative sunburn. The frequency of symptoms was recorded at various parts of the canopy (N, E,W, S, and lower canopy, upper canopy) and on the cluster (terminal, lateral). Cultivar susceptibility varied between 0.30 and 5.65% on M.9 rootstock, ‘Granny Smith’ seemed to be the most susceptible cultivar whereas relatively low percentage of damaged fruit was observed for ‘Gloster’. On MM.106 and seedling rootstocks, damage level was significantly lower than on M.9. Remarkable differences were not observed in the share of the three sunburn types between cultivars. The most common symptom observed was sunburn browning. Far less fruit was affected by sunburn necrosis and photooxidative sunburn. Photooxidative sunburn symptoms were not found on ‘Granny Smith’ and ‘Gloster’ fruits on MM.106 rootstock. Latter cultivar did not show sunburn necrosis symptoms either. With increasing growing vigor of the rootstocks the share of sunburn browning increased. Fruits with sunburn symptoms were found in a great majority on theW quadrant of the trees. This was true for all cultivars. Remarkable differences in the location within the canopy of affected fruits between the three types of sunburn were not observed. Specific distribution of sunburned fruit was observed along the vertical axis of the canopy, too. Most of the damaged fruit were found in the upper canopy. This is particularly true for trees on vigorous stocks such as MM.106 and seedling. On M.9 rootstock, depending on cultivars 5.9 to 38.9% of sunburned fruit was located in the lower canopy. Most common symptom in the lower canopy was the sunburn browning, however symptoms of sunburn necrosis were not found at lower canopy level. Low rate of photooxidative sunburn was observed such lower canopy conditions. Sunburn incidence was very similar on king or side fruit. Significant differences were not found in the share of each sunburn types between fruit positions on the cluster. This was not influenced by rootstocks either.